Pengaruh penggunaan substrat yang berbeda terhadap daya tetas telur dan sintasan hidup larva ikan lele sangkuriang (Clarias sp) - Arunde, Edwar; Sinjal, Hengki J; Monijung, Revol D. D (e-Journal BUDIDAYA PERAIRAN, 2016)
This  research aimed to study the influence of  different substrats on fertility and survival of catfish larva (Clarias Sp). This Research was conducted at Tatelu Village of  North Minahasa regency,  Province of North Sulawesi.  Experimental design used was Complete Randomized Design with four treatments including ijuk, Hydrilla, plastic rope, and control (without substrat), each with three replication. The result of this research showed that ijuk gave  significant effect on fertility and survival of  larva.   Fertility and survival of larva in this substrat achieved 77.58% and 87.33%  each. Keywords : Fertility, survival rate, larva, Clarias sp